2017
DOI: 10.1126/sciimmunol.aan2946
|View full text |Cite
|
Sign up to set email alerts
|

An immune clock of human pregnancy

Abstract: The maintenance of pregnancy relies on finely tuned immune adaptations. We demonstrate that these adaptations are precisely timed, reflecting an immune clock of pregnancy in women delivering at term. Using mass cytometry, the abundance and functional responses of all major immune cell subsets were quantified in serial blood samples collected throughout pregnancy. Cell signaling–based Elastic Net, a regularized regression method adapted from the elastic net algorithm, was developed to infer and prospectively va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
397
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 414 publications
(475 citation statements)
references
References 45 publications
29
397
0
9
Order By: Relevance
“…Instead of keeping immune suppression, maternal immunological states actively adapt to be changed with the growth and development of fetus at different gestational stage: from a pro-inflammatory state (beneficial to the embryo implantation and placentation) in the first trimester to an antiinflammatory state (helpful for the fetal growth) in the second trimester, and finally reaching a second pro-inflammatory state (preparing for the initiation of parturition) in the third trimester . Recently, Aghaeepour and colleagues (Aghaeepour et al,2017) suggested a precise timing of immunological events in peripheral blood that occurred during full-term pregnancy, named "immune clock." They found that pregnancyinduced a robust and progressive increase in endogenous STAT5ab signaling across J o u r n a l P r e -p r o o f multiple T cell subsets, including CD25 + FoxP3 + Treg cells, naïve and memory CD4 + and CD8 + T cells, and γδ T cells.…”
Section: The Role Of Maternal Immune Responses To Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of keeping immune suppression, maternal immunological states actively adapt to be changed with the growth and development of fetus at different gestational stage: from a pro-inflammatory state (beneficial to the embryo implantation and placentation) in the first trimester to an antiinflammatory state (helpful for the fetal growth) in the second trimester, and finally reaching a second pro-inflammatory state (preparing for the initiation of parturition) in the third trimester . Recently, Aghaeepour and colleagues (Aghaeepour et al,2017) suggested a precise timing of immunological events in peripheral blood that occurred during full-term pregnancy, named "immune clock." They found that pregnancyinduced a robust and progressive increase in endogenous STAT5ab signaling across J o u r n a l P r e -p r o o f multiple T cell subsets, including CD25 + FoxP3 + Treg cells, naïve and memory CD4 + and CD8 + T cells, and γδ T cells.…”
Section: The Role Of Maternal Immune Responses To Covid-19mentioning
confidence: 99%
“…Innate immune cells, such as NK cells and monocytes, respond more strongly to viral challenges, while some adaptive immune responses are down-regulated during pregnancy, e.g. decreased numbers of T cells and B cells (Aghaeepour et al,2017). Besides, during pregnancy, the upper respiratory tract tends to be swollen by a high level of estrogen and progesterone, and restricted lung expansion makes the pregnancy woman susceptible to respiratory pathogens.…”
Section: The Role Of Maternal Immune Responses To Covid-19mentioning
confidence: 99%
“…10 Although this important study reveals the scale of the immunomodulation that occurs during pregnancy, it remains unknown which of these changes is driven specifically by exposure to fetal alloantigen (ie, alloimmunization) or whether these changes occur because of other antigen nonspecific mechanisms. 10 Although this important study reveals the scale of the immunomodulation that occurs during pregnancy, it remains unknown which of these changes is driven specifically by exposure to fetal alloantigen (ie, alloimmunization) or whether these changes occur because of other antigen nonspecific mechanisms.…”
Section: Pre Valen Ce Of Preg Nan C Y Alloimmuniz Ationmentioning
confidence: 99%
“…). Changes in the maternal adaptive immune include decreased Th1/Th17 and increased Th2/Treg responses . Changes in maternal innate immune responses include increased surface expression of CD11a, CD11b, CD49d, CD14, CD64, and CD54 on monocytes during third trimester .…”
Section: Introductionmentioning
confidence: 99%